Accelerating hole extraction by inserting 2D Ti3C2-MXene interlayer to all inorganic perovskite solar cells with long-term stability. Issue 36 (9th September 2019) - Chen, Taotao; Tong, Guoqing; Xu, Enze; Li, Huan; Li, Pengcheng; Zhu, Zhifeng; Tang, Jianxin; Qi, Yabing; Jiang, Yang
Abstract : MXenes have been demonstrated as a potential candidate in the field of photovoltaics and energy storage owing to their high transmittance, metallic conductivity and tunable work function. Abstract : MXenes have been demonstrated as a potential candidate in the field of photovoltaics and energy storage owing to their high transmittance, metallic conductivity and tunable work function. In this work, we introduce a two-dimensional (2D) structure of Ti3 C2 -MXene nanosheets into all inorganic CsPbBr3 solar cells as an interlayer to realize a better interfacial energy level alignment, which helps to eliminate the energy level mismatch, accelerate the hole extraction and reduce the recombination at the interface of perovskite/carbon electrode. In addition, the functional groups such as O existing in the surface of Ti3 C2 -MXene nanosheets also provide strong interactions between the MXene and under-coordinated Pb atoms, which remarkably reduces the deep trap defects in the CsPbBr3 films. The device with the Ti3 C2 -MXene interlayer shows an impressive initial power conversion efficiency of 9.01% and long-term stability for over 1900 hours in a moisture environment and more than 600 hours under thermal conditions.